Pelatihan dan Pengembangan Media Imersif Augmented Reality Pada Pembelajaran Tata Cara Wudhu di SD Muhammadiyah 2 Tulangan Sidoarjo - Lutvi Azizah, Nuril; Taurusta, Cindy; Faizah A, Nadtasya; Lailil S, Masyitah; Atmaranti, Julia (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
The limited utilization of digital technology in teaching ablution procedures at the elementary school level has resulted in predominantly conventional learning practices that are less engaging for students. This community service activity aimed to enhance teachers’ capabilities in developing and implementing immersive learning media based on Augmented Reality technology to improve students’ understanding of proper ablution procedures. The program was conducted at SD Muhammadiyah 2 Tulangan through a structured approach consisting of theoretical sessions, mentoring, hands-on practice, as well as monitoring, and evaluation using observation, pre-test, and post-test instruments. Participants included six assisting teachers and thirty lower-grade students divided into three groups: ten first-grade students, ten second-grade students, and ten third-grade students. The result indicated a significant improvement in teachers’ digital competency, with the percentage of teachers able to operate digital learning media increasing from 78% to 93%. Student participation also increased from 78% before the implementation of the media to 90% afterward. Each student group demonstrated a more systematic understanding of ablution movement and sequences, accompanied by heightened learning enthusiasm. This activity confirms that the active involvement of teachers and students in the development and implementation of immersive learning media effectively enhances the quality of religious education in elementary schools and supports sustainable technology-based learning transformation.